Clinical and biochemical presentation of sarcoidosis with high and normal serum angiotensin-converting enzyme. (2nd November 2018) - Sejdic, A; Graudal, N; Baslund, B
Abstract : Objectives : The presentation of sarcoidosis can involve symptoms from all organs and the diagnosis is therefore often difficult. A raised serum level of serum angiotensin-converting enzyme (sACE) can be detected in 41–58% of patients. However, whether the sACE level per se reflects the severity of the sarcoid inflammation at the onset of the disease is not well described. The purpose of this study was to investigate the clinical and laboratory significance of high versus normal sACE levels in sarcoidosis. Method : Journal data were retrospectively extracted from 101 patients from our clinic. Clinical and biochemical data were compared between patients with high sACE levels (> 115 U/L) on at least one occasion and normal sACE levels (< 115 U/L). Results : In total, 48% (n = 48) of the patients had high ACE and 52% (n = 53) had normal ACE. The most common extrapulmonary manifestation for both groups was arthritis, followed by skin and eye involvement, but none of these differed between the two groups. Serum ionized calcium was significantly higher in the high sACE group, with a correlation coefficient of 0.112 (p = 0.460). Conclusion : Our study demonstrates that serum ionized calcium is significantly higher in the high sACE group but there was no statistical correlation to sACE. No other clinical or biochemical differences were observed.